Turning Microstructure in Block Copolymer Membranes: A Facile Strategy to Improve CO2 Separation Performance - Jing Wei; Min Deng; Zikang Qin; Weiyi Zhao; Yujie Li; Roman Selyanchyn; Hongyong Zhao; Jie Dong; Dengguo Yin; Yuanfa Zhuang; Liyuan Deng; Lin Yang; et al. (Advanced Science)
Abstract To mitigate global climate change, the development of membranes with high CO2 permeability and selectivity is urgently needed. Here, a simple and effective non‐solvent‐induced microstructure rearrangement (MSR) technique is proposed to enhance the gas separation performance of Pebax 2533 membranes. By immersing Pebax 2533 membranes in amino acid salt solutions to induce MSR, the CO2 permeability of the optimized Pebax 2533‐GlyK 10 wt.% membrane reached 1180 Barrer, a 4.5‐fold increase compared to the original membrane, without compromising CO2/N2 selectivity. Moreover, the MSR membrane maintains stable gas separation performance for nearly 500 days, demonstrating excellent long‐term stability. Furthermore, applying the MSR technique to thin‐film composite (TFC) membranes revealed that both Pebax 2533/polyvinyl chloride (PVC) hollow fiber (HF) TFC membranes and Pebax 2533/polyacrylonitrile (PAN) flat‐sheet TFC membranes exhibited significantly enhanced CO2 permeance under the treatment of DI water. Characterization results indicated that the chemical‐physical properties of the membranes before and after MSR are nearly unchanged, suggesting that the non‐solvent‐induced MSR is a promising technique for next‐generation membrane development for carbon capture.